Analisa perbandingan Kuat Tekan Beton Semen PCC Dan Semen Tipe 1 Terhadap Pemakaian Sikament NN - Istighfar, Irfan; Kurniawandy, Alex; Ermiyati, Ermiyati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The state of the art in cement manafacturer produces cement that can give high quality concrete and environmentally sustainable, which of product is Portland Composite Cement (PCC). This research aim to find solution to increase the compressive strength of PCC approaching the value of Ordinary Portland Cement (OPC) Compressive Strength. One of the solution is by adding Sikament NN into the concrete mixture. Samples are in Cylindrical shape 15 cm diameter and 30 cm height in age of test 7, 28 and 91 day with 3 samples per each. Design of mix composition use ACI method with w/c 0,4 ; 0,35 ; 0,3. The initial time for OPC is 92,99 minute and the final setting time is 150 minute, the initial time for PCC is 119,17 minute and final setting time is 165,5 minute. The initial time for OPC with Sikament NN is 222,5 minute and final setting time is 285 minute, the initial time for PCC with Sikament NN is 247,5 minute and final setting time is 300 minute. The result of compressive strength at age of samples of 7, 28 and 91 days with FAS of 0,4; 0,35; and 0,30; shows higher compressive strength of type 1 cement compared to PCC cement’s compressive strength and higher compresive strength of type 1+Sikament NN compared to PCC+Sikament NN’s compresive strength and higher compresive strength of PCC+Sikament NN compared to type 1 cement’s compressive strength. Keyword : Compressive Strength, PCC cement, Type 1 cement , initial time, Sikament NN